The Impact of Social Media Use on Chinese Tourists’ Intention to Visit an Internet Celebrity City: An Application of Theory of Planned Behavior - Wu, TANG; Mohamed, Ahmad Edwin bin; Hongjun, FAN (International Journal of Membrane Science and Technology, 2023)
With the rise of social media and online content platforms in China, many cities have become internet celebrities in recent years. The theory of planned behavior (TPB) model will be used to look at the variables that could affect tourists’ visit intention to these cities. Using the TPB model, it also aimed to determine how social media use affected internet celebrity city(ICC) tourism. This research employed partial least squares structural equation modelling (PLS-SEM) for the analysis. From the results, we could see that attitude, subjective norm, and perceived behavior control all had an impact on tourists’ intention, with subjective norm having the biggest impact. Tourists’ use of social media also influenced tourists’ visit intention, while frequency of social media use did not have a significant moderating effect between subjective norm and visit intention. The findings can be used by organization marketers and city governors to help them make better business decisions.